Vector Space on the Binomial Coefficients in Combinatorial Geometric Series - Chinnaraji Annamalai; Antonio Marcos de Oliveira Siqueira (The Journal of Engineering and Exact Sciences)
A vector space is a group of objects that is closed under finite vector addition and scalar multiplication. This paper discusses a vector space under addition and multiplication of binomial coefficients defined in combinatorial geometric series. The combinatorial geometric series is a geometric series with binomial coefficients that is derived from the multiple summations of geometric series. This idea can enable the scientific researchers to solve the real world problems.